Optimization of Sago Dregs as Pellet Feed of Broiler in Tanjung Meranti Islands Village: Optimalisasi Ampas Sagu Sebagai Pakan Pellet Ayam Broiler Di Desa Tanjung Kepulauan Meranti - Solfan, Bakhendri; Rahmadani, Elfi; Harahap, Anwar; Rodiallah, Muhamad; Juliantoni, Jepri; Adelina, Triani; Mucra, Dewi Ananda; Irawati, Evi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Tanjung Kepulauan Meranti Village, Riau has production large sago plants so that the waste is used as animal feed with pellet technology. The purpose of this service to utilize sago pulp that has not been used as feed of broiler. The service method uses PAR, which is a method of involving community groups as  whole in research activities so that positive social change occurs. The results show that community groups are very enthusiastic about participating in community service activities with indicators the ease with which community groups understand the material provided. Some of  the material conveyed that sago pulp can be fermented to increase nutritional value, especially protein and reduce crude fiber, then fermented sago pulp can be used as broiler feed pellets. In conclusion, sago pulp can be used as a pellet product at a low price as an alternative to commercial pellet  feed to reduce costs in broiler  farming